Does Policy Influence Hollow Out Public Managers' Political Neutrality?. Issue 6 (July 2022) - Åström, Joachim; Olsson, Jan; Hysing, Erik
Consequences of public officials' policy influence have been at the center of debates on political–administrative relations. Based on a survey of public managers in Swedish local government ( N = 1, 430), this study examines whether policy politics hollows out political neutrality. The analysis shows that although managers are highly involved in policy politics, attitudinal support for the neutrality principle is strong. The enquiry into behavioral intentions shows more variation. In relation to a set of dilemmas, most managers would defend neutral competence, but significant minorities would also act for more partisan reasons. However, we find no empirical evidence that policy influence undermines political neutrality.